2020
DOI: 10.3390/polym12122980
|View full text |Cite
|
Sign up to set email alerts
|

Fused Deposition Modeling of Polyamides: Crystallization and Weld Formation

Abstract: International newspapers and experts have called 3D printing the industrial revolution of this century. Among all its available variants, the fused deposition modeling (FDM) technique is of greater interest since its application is possible using simple desktop printers. FDM is a complex process, characterized by a large number of parameters that influence the quality and final properties of the product. In particular, in the case of semicrystalline polymers, which afford better mechanical properties than amor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…However, the use of this technology for practical applications is significantly affected by the anisotropy of the mechanical properties found in the printed products [ 10 , 11 , 12 ]. In particular, it has been found that the ultimate tensile strength is higher in the direction parallel to that of the filament deposition, while it strongly decreases in the perpendicular direction [ 13 , 14 , 15 ]. It is therefore clear that the final mechanical properties of the manufactured articles are strongly correlated to the quality of the bond that is established between the adjacent layers [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of this technology for practical applications is significantly affected by the anisotropy of the mechanical properties found in the printed products [ 10 , 11 , 12 ]. In particular, it has been found that the ultimate tensile strength is higher in the direction parallel to that of the filament deposition, while it strongly decreases in the perpendicular direction [ 13 , 14 , 15 ]. It is therefore clear that the final mechanical properties of the manufactured articles are strongly correlated to the quality of the bond that is established between the adjacent layers [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is known that harsh printing conditions can largely influence the final mechanical properties. In previous works, it has been demonstrated that the use of low nozzle temperatures and higher printing speeds significantly reduce the quality of the weld [ 15 , 24 , 25 ]. By combining birefringence measurements and tensile tests with results from a continuum model, Costanzo et al highlighted that the cause of the low weld strength for stronger processing conditions is the molecular orientation present at the interface between the layers [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The negative impact on bond strength can be attributed to the residual alignment due to orientation of polymer chains upon extrusion from the print nozzle. If the residual alignment cannot relax prior to solidification, insufficient entanglements can be formed leading to poorer interlayer adhesion [ 50 , 51 ]. The print speeds employed in this study are most likely too low to actually induce a significant change in interlayer bond strength through alignment effects upon extrusion.…”
Section: Resultsmentioning
confidence: 99%
“…However, a higher T build plate has been found to considerably enhance the attained degree of crystallinity and lead to thicker lamellae through an annealing effect by the heated build plate, which improves mechanical strength when loaded along the layer deposition direction [49]. Costanzo et al (2020) have reported a significant effect of print speed (v print ) through its impact on molecular orientation upon extrusion leading to a decrease in weld strength. Residual molecular alignment at the weld zone was found to be alleviated by increasing T liquefier or decreasing v print [50,51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation